2020
DOI: 10.1101/2020.10.14.338699
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sonogenetic control of mammalian cells using exogenous Transient Receptor Potential A1 channels

Abstract: Our understanding of the nervous system has been fundamentally advanced by light- and small molecule-sensitive proteins that can be used to modify neuronal excitability. However, optogenetics requires invasive instrumentation while chemogenetics lacks temporal control. Here, we identify a candidate channel that confers sensitivity to non-invasive ultrasound on millisecond timescales. Using a functional screen, we find that human Transient Receptor Potential A1 (hsTRPA1) increases ultrasound-evoked intracellu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 95 publications
3
18
0
Order By: Relevance
“…These data suggest that we are unlikely to cause cavitation and cell viability remains unaffected as shown by prior work with similar stimulus parameters. [ 18 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that we are unlikely to cause cavitation and cell viability remains unaffected as shown by prior work with similar stimulus parameters. [ 18 ]…”
Section: Resultsmentioning
confidence: 99%
“…It is noninvasive and has a high spatiotemporal resolution (<1 mm and <1 ms) in comparison to existing techniques. Improvements in the spatial resolution through transfection of mechanosensitive proteins currently come at the cost of a minimally‐invasive procedure to directly inject the vector into the target tissue, [ 18 ] though there may soon be non‐invasive alternatives. [ 19 ] The spatial resolution of ultrasound is governed by the wavelength of operation and is about 1.5 mm at 1 MHz in tissue.…”
Section: Introductionmentioning
confidence: 99%
“…It is non-invasive and has a high spatiotemporal resolution. Improvements in the spatial resolution through transfection currently come at the cost of a minimally-invasive procedure to directly inject the vector into the target tissue [18], though there may soon be non-invasive alternatives [19]. The spatial resolution of ultrasound is governed by the wavelength of operation and is about 1.5 mm at 1 MHz in tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Sonogenetics relies on genetically engineering cells to be more sensitive to mechanical stimuli using membrane bound proteins 20,21 . This technique eliminates the need for focused ultrasound by ensuring that targeted neural circuits are the only ones that will respond to an ultrasound stimulus.…”
mentioning
confidence: 99%
“…This technique eliminates the need for focused ultrasound by ensuring that targeted neural circuits are the only ones that will respond to an ultrasound stimulus. Recent work has revealed that one protein in particular, human transient receptor potential A1 (hsTRPA1), produces ultrasound-evoked responses in several cell types 21 . One limitation of sonogenetics is that existing transducers producing planar or focused ultrasound are unsuitable .…”
mentioning
confidence: 99%